Speech action patterns of Indonesian at multi-language campus - Andiopenta Andiopenta; Suyadi Suyadi (PT. MAWAMEDIA JAYAMUSTA BUANASIHA, 2024)
This study aims to describe the types and functions of speech acts constructed by Indonesian Language and Literature Education students at the Teaching and Education Faculty, Universitas Jambi, who have multilingual backgrounds. This research is a qualitative descriptive study. Data were collected from 30 informants. Data was collected using free listening techniques in various settings on the campus, as well as recordings and field notes. Data were analyzed using the flow technique from Miles and Huberman through the steps of data reduction, data presentation, and drawing conclusions. The data validation technique used theory and method triangulation techniques. The results of the research can be seen in events of students of Indonesian Language and Literature Education, Teaching and Education Faculty, Universitas Jambi, which is multilingual, including speech acts; (1) commission, (2) assertive, (3) declarative, (4) expressive, and (5) directive. Likewise, the function of the speech act that is revealed is a function; (1) competitive, (2) fun, (3) cooperative, (4) contradictory. The students’ multilingual background in uncovering the types and functions of speech acts consists of speakers of the language; (1) Bugis, (2) Batak, (3) Malay Jambi, (4) Javanese, (5) Palembang, (6) Kerinci, and (7) Minangkabau. The speech patterns built by speakers of different mother tongues can be seen and the cultural background of each ethnicity is very influential. Their cultural different background brings about different styles of language. The language culture of Bugis, Batak, and Palembang speakers feels more assertive, and vulgar and shows a slightly harsh tone. Whereas, those with a cultural background in Minangkabau, Kerinci, Javanes, and Jambi Malay languages feel more relaxed and softer. This can be seen both in each type of speech act, as well as in terms of the expression of the function of the speech act. However, when they are faced with the reality of being multi-language, they are forced to use Bahasa Indonesia, and in turn, they become a reflection of patterns of speech acts in Bahasa Indonesia as well as a profile of Indonesian sociolinguistics.